A population-based registry study on psoriasis-associated burden of disease in Finland - Ukkola-Vuoti, Liisa; Klåvus, Anton; Toppila, Iiro; Hällfors, Jenni; Veijalainen, Lauri; Mälkönen, Tarja (Frontiers in Medicine, 2025)
IntroductionDespite advancements in treatment, unmet needs persist for patients with plaque psoriasis (PSO). This study characterized PSO patients who were initiating or switching biologic medications, with or without prior biologic use, and highlighted the unmet needs due to medication switches and concomitant treatments. The impact of biologic therapy initiation was assessed through changes in healthcare resource utilization (HCRU), sick leave, and disability pensions.MethodsThis study utilized electronic healthcare data of adult patients with PSO and reimbursed biologic medication purchases made between 2013 and 2021 in Finland. Patients were followed from the day of first biologic treatment purchase (first biological cohort) or switch (switchers) until 2022 or death/loss of follow-up.ResultsA total of 2,437 patients with PSO and biologic medication purchases were investigated. Of this total, 14.2% (n = 345) were switchers, and 85.8% (n = 2,092) comprised the first biological cohort. Among the first biological cohort, 12.5% [95% confidence interval (CI): 11.1, 13.9] had switched to other biologic medications 1 year after initiation. Work absences started to accumulate before the initiation of the first medication in the first biological cohort, followed by a subsequent decrease, while the accumulation remained modest and linear in shape among the switchers. The proportion of patients aged <65 on disability pension was higher among the switchers compared to the first biological cohort (7.8% (n = 27) and 6.6% (n = 138), respectively). A total of 86 first biological patients (4.1%) and 11 (3.2%) switchers were receiving disability pension before the biologic treatment was initiated. The number of all-cause secondary healthcare outpatient contacts per year (11.1 vs. 7.4 per patient; p < 0.001) and disease-related inpatient days (0.46 vs. 0.16 per patient; p < 0.001) was lower 1 year after the initiation of biologic treatment in the first biological cohort compared to the time before biologic treatment. The decrease in the disease-related any-type contact cost per year for the first biological cohort was significant, from €2,098 (95% CI: 1,975, 2,221) to €1,094 (95% CI: 1,012, 1,176; p < 0.001). No significant reduction was observed in the HCRU of switchers.DiscussionThis study highlights the need for timely treatment and underscores the significant unmet needs among patients with PSO. Further studies are needed to evaluate the overall benefits of early utilization of highly effective treatments.